Efficacy Of Polymerase Chain Reaction Over Ziehl-Neelsen Staining In The Diagnosis Of Mycobacterium Tuberculosis - HUMERA Q. F. ANSARI,; MAIMOONA MUSTAFA, (International Journal of Pharma and Bio Sciences, 2011)
Tuberculosis, one of the oldest diseases tormenting humankind, is especially rampant in developing countries like India, with a prevalence as high as 30%. Yet tuberculosis control has not been achieved due to lack of rapid identification methods. The objectives of this study were to examine microscopically all specimens after Ziehl-Neelsen staining, isolate genomic DNA from samples, perform PCR amplification using specific primers, and compare results obtained by both methods. Sixty clinical samples, which included 40 sputa and 10 samples each of pleural and ascitic fluid, from patients clinically suspected for tuberculosis were subjected to AFB staining and detection of Mycobacterium tuberculosis using PCR. Of the 40 cases, 16 were found positive by microscopy and 30 were found positive by PCR. Of the 20 extrapulmonary cases, 4 were found positive by microscopy and 16 were found positive by PCR, proving the superiority of PCR in the early detection of Mycobacterium tuberculosis.